Does informal finance matter for micro and small businesses in Africa? - Stephen Mago; Florah Sewela Modiba (Small Business International Review)
Globally, micro and small businesses require finance to support their business activities. Most of them have low profits because of the lack of support from the formal financial system. Micro and small businesses in developing countries have a dire need for financing start-ups and existing business operations. The lack of support from the formal financial system and the government forces them to explore other financial support mechanisms, making it important to investigate alternative financial channels. This paper investigates whether informal finance matters for micro and small businesses. We used a systematic literature review to answer the predetermined research question. Thirty (30) primary studies were surveyed to establish the importance of informal finance for micro and small businesses. The findings show that informal finance is a workable alternative for micro and small businesses. It supports business start-ups, existing businesses and enhances business growth, business owners’ livelihoods and livelihoods in their communities. Informal finance models can be improved to work as small business promotion tools. The original value of the paper is based on the use of a systematic literature review to assess whether informal finance matters for micro and small businesses and connect theories with emerging themes. It further contributes to the debates on the importance of informal finance and contributes to future lines of research on informal finance.